Overview of Acute Kidney Injury (AKI) in the Intensive Care Unit: Observational Study at Prof. Dr. I.G.N.G Ngoerah General Hospital, Denpasar, Indonesia - Pontisomaya Parami; Tjokorda Gde Agung Senapathi; Gede Wirya Kusuma Duarsa; Pramana, Putu Bagus Gin Gin (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Acute kidney injury (AKI) is a serious clinical syndrome with complications that can be life-threatening. AKI is associated with increased length of stay and mortality in patients in the intensive care unit (ICU). This study aims to determine the incidence and characteristics of AKI in ICU patients at Prof. Dr. I.G.N.G Ngoerah General Hospital Denpasar. Methods: This descriptive observational research was conducted by collecting data from medical records of ICU patients for three months. Data were analyzed to determine the incidence of AKI, stage of severity, and mortality rate. Results: Of the 388 patients treated in the ICU, 87 (22.37%) experienced AKI. The mortality rate in AKI patients was 12.9% (n=50). A total of 11.05% (n=25) of AKI patients were classified as stage 1, 5.91% (n=17) as stage 2, and 5.40% (n=8) as stage 3. Conclusion: The incidence of AKI in the ICU of Prof. Dr. I.G.N.G Ngoerah General Hospital Denpasar. is quite high (22.37%). AKI is associated with a significant mortality rate (12.9%). This study provides a preliminary description of the incidence and characteristics of AKI in the ICU of this hospital, which may be useful for improving the quality of patient care and prevention of AKI.